Aerodynamic comparison of slotted and non-slotted diffuser casings for Diffuser Augmented Wind Turbines (DAWT). (June 2022) - Sridhar, Surya; Zuber, Mohammad; B., Satish Shenoy; Kumar, Amit; Ng, Eddie Y.K.; Radhakrishnan, Jayakrishnan
Abstract: The ability of Horizontal & Vertical Axis Wind Turbine (HAWT & VAWT) to harness the incoming wind is limited due to several factors such as structural constrains, fatigue problems, geographical and ecological issues, noise pollution, vibrational & acoustic losses. Diffuser Augmented Wind Turbine (DAWT) exploits the concepts of velocity augmentation to maximize power production efficiently when compared to conventional approach. The optimization of the geometric parameters can help the augmentation capability of the diffuser. This study investigates the aerodynamic effect of slits on diffuser casings and the performance of slotted and non-slotted diffuser casings is compared using 3D CFD analysis and validated experimentally. The performance of the studied diffusers is analysed in terms of velocity at the rotor plane, augmentation ratio, and swallowed mass flow rate. At tip speed corresponding to 62 m/s, the performance parameters of slotted DAWTs showed an increase by 27.4% and 46.8% compared to non-slotted DAWTs and open turbines, respectively. It is also observed that the inclusion of slotted and non-slotted diffusers enclosing the rotor resulted in an average augmentation of 2.01 and 1.36 in both power and torque produced, respectively. Highlights: DAWT have proven to overcome the Betz limit and reduce tip losses & noise. Addition of slots to diffuser casing has shown to increase both torque and power. Slotted DAWTs have shown to produce higher power with greater efficiency.